ダイチョウキン ヲ シヒョウ トシタ ショウワキチ シュウヘン ノ オセン ニ カンスル チョウサ ケンキュウ - 渡部, 和彦; ワタナベ, カズヒコ; 朝比奈, 一男; アサヒナ, カズオ; 鈴木, 達夫; スズキ, タツオ; 佐々木, 武二; ササキ, タケジ; 合田, 朗; ゴウダ, アキラ; Watanabe, Kazuhiko; Asahina, Kazuo; et al. (国立極地研究所, 1977)
P(論文) 昭和基地周辺地域における人為汚染の実態を明らかにするために,腸内細菌(大腸菌)を指標とした細菌学的調査を行った.調査対象は,飲用水を中心に,水道,土壌,大気,雪および氷である.その結果,以下のことについて明らかとなった.第15次隊医学担当隊員により設定された,定観測地点の土壌中から,腸内細菌(大腸菌)は検出されなかった.しかし,飲用水,水道水からはしばしば検出された.水道水への細菌汚染の経路が追求され,人為汚染経路が明らかにされた.現在のところ,病原細菌による汚染はなかったが,隊員の健康を守るために,適切な予防対策が講じられることが望まれた.人為汚染の他の生物への影響が同様に細菌学的方法で調査され,一羽のオオトウゾクカモメの腸管内から大腸菌が検出された. Bacteriological investigation of pollution caused by human being was conducted at Syowa Station. Special attention was paid to the contamination of Enterobacteriaceae (E. coli). The soil, water, air, snow and ice were examined both at Syowa Station and Mizuho Camp. The following results were obtained. E. coli was not detected at the bacteriological pollution monitoring points which were set up by the 15th Japanese Antarctic Research Expedition (JARE-15). On the other hand, in the waterworks and in the drinking water at Syowa Station, E. coli was detected from many parts. But no pathogenic bacteria have been found so far. However, some means of effective prevention should be considered to ensure healthy living at Syowa Station. Some birds were also examined in terms of bacteriological pollution. departmental bulletin paper